Potensi Antihiperglikemia Kombinasi Ekstrak Daun Salam dan Ikan Gabus - Razoki, Razoki; Simanjuntak, Nerly Juli Pranita (Jurnal Indah Sains dan Klinis, 2024)
Background: Flavonoids, as secondary metabolites found in bay leaves, exhibit antioxidant properties that help prevent damage to pancreatic β cells by neutralizing free radicals responsible for cell injury. Protein from snakehead fish plays a role in regulating blood sugar levels by inhibiting the α-glucosidase enzyme. Objective: This study aimed to assess the potential of combining the two extracts to lower blood sugar levels in mice. Method: Six groups were used in the study, each receiving a 250 mg/kg BW dose and 40% glucose inducer: Aquades (A), ethanol extract of bay leaves (EEDS), snakehead fish extract (EIG), and combinations of ethanol extracts of bay leaves and snakehead fish (EEDS-IG) in ratios of 1:1, 2:1, and 3:1 (w/w). Results: The study revealed that EEDS and EIG reduced blood sugar levels by 12.14%, 66.9%, 55.0%, 69.3%, 69.7%, and 69.3% at the 120th minute, respectively, for each group. Conclusion: The combination of EEDS and EIG has the potential to reduce blood sugar levels, particularly at a 2:1 ratio